A Coupled Modelling Method for the Evaluation of the Impact of Pavement Solar Collector on Urban Air Temperature and Thermal Collection. Issue 1 (19th February 2021) - Xu, Weijie; Jimenez-Bescos, Carlos; Pantua, Conrad Allan Jay; Calautit, John; Wu, Yupeng
The Urban Heat Island (UHI) effect is a phenomenon whereby urban areas become warmer than their surrounding rural areas, due to the replacement of vegetation and soil with surfaces such as asphalt and concrete. The asphalt pavement surfaces tend to absorb a large amount of heat through solar radiation and increase the air temperature, which affects the operation of building heating and cooling systems, causing environmental problems and thermal discomfort. However, this energy can be collected by water circulated through buried copper pipes to cool down temperatures and be stored for other usages. This work aims to develop a method for determining the optimum areas to locate pavement solar collector (PSC) systems and simulate the reduction of ambient air and surface temperature by using a coupled computational modelling approach. Discrete ordinate model and solar-ray tracing were utilised for solar radiation effect modelling in the 3D simulation. Furthermore, the PSC prototype was developed, and lab-scale experiments were carried out for validation. Based on the simulated conditions, in the unshaded area, the asphalt slab's near-surface temperature was reduced by up to 10°C and the outlet water temperature increased by about 5°C. At the pedestrian height level, the air temperature was reduced up to 4.6°C. This study further expands the investigation of the variation of outdoor conditions such as air temperature and solar radiation. The results showed that the proposed method could be used to optimise the pavement solar collector's positioning to reduce urban surface and air temperature.